If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + 4 = -5(6x + -3) Combine like terms: 11 + 4 = 15 15 = -5(6x + -3) Reorder the terms: 15 = -5(-3 + 6x) 15 = (-3 * -5 + 6x * -5) 15 = (15 + -30x) Add '-15' to each side of the equation. 15 + -15 = 15 + -15 + -30x Combine like terms: 15 + -15 = 0 0 = 15 + -15 + -30x Combine like terms: 15 + -15 = 0 0 = 0 + -30x 0 = -30x Solving 0 = -30x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30x' to each side of the equation. 0 + 30x = -30x + 30x Remove the zero: 30x = -30x + 30x Combine like terms: -30x + 30x = 0 30x = 0 Divide each side by '30'. x = 0 Simplifying x = 0
| -7z+12z^2-12=0 | | 4(x+3)-(6n+6)= | | 39+4y-16=17y-13-4y | | 6(x+4)-9=2x+4(5+x) | | y-5=-5(x+6) | | 20x-16=20x+7 | | 4(x+12)-(6n+6)= | | 2x+7y=k+8 | | 3y^2+65=2y^2+127 | | 20x-16=20x+4 | | 0.85x+0.05(10-x)=0.10(-27) | | -7(3x-3)+6=-21x+27 | | 3x^2+3y^2+15y+9x+12=0 | | 2x(3x-9)-4=2(x-3) | | 6(18.5)-3=x | | 11r^2+28=0 | | -7(3x-3)+6=-21x+7 | | (5+x^4)-(3x^4+4x)=0 | | h(x)=x^2+9x+8 | | 2(-3y-1)+(2y+7)=a | | 2x+5+6x-3+30=180 | | 40.7=5b | | -3(x+9)+6x=-6 | | 3(x^3+2x^2+8x+36)=0 | | -9d-8=154 | | -0.10(13)+0.20x=0.05(x-14) | | 5(3x-6)-4=5(x-4)+76 | | 8n^2=24n+320 | | Y-8=37-7y | | 5ab+7ac-ab+3ab= | | 20x-16=20x+16 | | 4y+0.5x=12 |